2018
DOI: 10.1097/md.0000000000011889
|View full text |Cite
|
Sign up to set email alerts
|

Different regimens of penicillin antibiotics given to women routinely for preventing infection after cesarean section

Abstract: Background:Varied regimens of penicillin antibiotics were given to women for preventing infection after cesarean section, but there is no study compares the effectiveness and safety of them.Methods:We searched MEDLINE, Embase, CENTRAL, CNKI, Wanfang, VIP, and CBM Database, and contacted experts in the field and searched reference lists of retrieved studies. We included randomized controlled trials comparing different regimens of penicillin antibiotics given to women after cesarean section. Two review authors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…The several risk factors related to surgical site infections should be concerned. Due to the continuous liberalization of China’s second child policy, the maternal age is uneven, and the women with older age have relatively poor tolerance to surgery and immunity, which is an important risk factor for surgical site infection after cesarean section [ 26 ]. Besides, during the surgery, a large amount of bleeding may occur, which may cause anemia and even hemorrhagic shock [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The several risk factors related to surgical site infections should be concerned. Due to the continuous liberalization of China’s second child policy, the maternal age is uneven, and the women with older age have relatively poor tolerance to surgery and immunity, which is an important risk factor for surgical site infection after cesarean section [ 26 ]. Besides, during the surgery, a large amount of bleeding may occur, which may cause anemia and even hemorrhagic shock [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not perform subgroup analysis, since the positive results of this study did not show heterogeneity. In addition, we believe that subgroup analysis will not get positive results because recent studies comparing antibiotic use between intravenous injection and lavage groups, as well as before and after umbilical cord clamping and skin incision, have reported no significant differences between drug deliveries [ 9 , 22 , 23 ]. Another recent meta-analysis that investigated the use of cephalosporin generations and penicillin types to prevent maternal infection after cesarean delivery also did not find significant differences between these subgroups [ 6 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have suggested a similar efficacy across different antibiotic dosages [ 7 , 8 ], there is limited evidence regarding the comparison of the efficacy of different antibiotic classes and dosages. An existing review that used meta-analysis to analyze studies suggested that cephalosporins and penicillins may have similar efficacy in preventing maternal infection after cesarean delivery [ 6 , 7 , 9 ]. However, this systematic review was published several years ago; hence, an update may be required.…”
Section: Introductionmentioning
confidence: 99%
“…Our low post‐caesarean superficial SSI rates might have been due to our anti‐infection practices at caesarean delivery comprising use of alcohol‐chlorhexidine solution for abdominal skin prep, 14 routine vaginal‐cervical cleansing with alcohol‐chlorhexidine solution, 15 prophylactic antibiotic administration prior to skin incision, 16 three doses of prophylactic broad spectrum intravenous antibiotics (cefuroxime and metronidazole), 17 delivery of placenta by cord traction, 18 subcutaneous and adipose tissue cleansing with alcohol‐chlorhexidine solution prior to skin closure 2 and exclusive use of subcuticular suture skin closure 19 . A recent publication from an urban public hospital in Penang, Malaysia of a retrospective chart review of 400 caesarean deliveries with completed data charts reported an SSI rate of 18.8% 20 …”
Section: Discussionmentioning
confidence: 99%